Vendor Held Stock (HVS) Implementation to Improve and Innovate Fuel Management System: Case Study at Prabumulih Field-Pertamina EP - Sulaeman, Haridito Rachmat; Firman, Aries F (The Indonesian Journal of Business Administration, 2012)
Management of fuel in PERTAMINA EP has not managed properly. The current system cannot guarantee the availability of fuel. Losses during storage and distribution exceed the allowable tolerance limits. Equipment, facilities, and infrastructure not meet existing standards as result in fuel consumption data at each location is not accurate. The above matter can lead to high operating costs and affect the company's image. For improvements things mentioned above, the first step is to conduct observation and data collection. The data was analyzed and identified what the potential problems. Potential problems are discussed for the problem solving expectations. After knowing the expectations of the solution designed a new concept of the fuel management system. One alternative designed concept is managing fuel by using a Vendor Held Stock system. After the comparison between the old fuel management concept with a new one, select a better concept fuel management and more profitable for the company. By applying good fuel management system, the problems faced in the management of fuel can be overcome Keywords: fuel management, fuel losses, the accuracy of usage, vendor held stock